Reactive Carbonyl Species and Protein Adducts: Identification Strategies, Biological Mechanisms and Molecular Approaches for Their Detoxification - Giancarlo Aldini; Alessandra A. Altomare (MDPI AG, 2021)
The Special issue is composed of 13 contributions: 9 research papers and 4 reviews [...]